2013
DOI: 10.1136/vr.101133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for canine epilepsy of unknown origin in the UK

Abstract: Epidemiological evaluation of canine epilepsy is an under-researched area. The objectives of this study were to estimate prevalence and investigate risk factors for epilepsy of unknown origin (EUO) among dogs attending primary veterinary practices in the UK. The clinical data analysed spanned a two-year period and included all dogs attending 92 primary veterinary clinics participating in the VetCompass project. Five hundred and thirty-nine EUO cases were identified giving a prevalence of 0.62% (95% CI 0.57% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(173 citation statements)
references
References 18 publications
4
160
1
8
Order By: Relevance
“…Previous studies have reported the incidence of epilepsy as 0.55–2% of all the dogs referred to veterinary hospitals 34, 35, 36. Our study demonstrated that 10% of dogs with TBI develop PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the incidence of epilepsy as 0.55–2% of all the dogs referred to veterinary hospitals 34, 35, 36. Our study demonstrated that 10% of dogs with TBI develop PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Practice selection required willingness to participate and use of an appropriately configured practice management system (PMS). Clinicians selected summary diagnosis terms at episodes of clinical care from an embedded VeNom Code list (21). Clinical data extraction from PMSs used integrated clinical queries (22) before uploading to a secure structured query language (SQL) database.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of this large data resource would allow DMVD prevalence to be estimated and major risk factors for the disease to be identified, as has been demonstrated for other disorders in companion animals 19, 20, 21…”
mentioning
confidence: 99%